2001
DOI: 10.1046/j.1365-2559.2001.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary squamous cell carcinoma of the thyroid gland: an entity with aggressive clinical behaviour and distinctive cytokeratin expression profiles

Abstract: Squamous cell carcinoma of the thyroid has aggressive clinical behaviour and characteristic CK expression pattern. p53 over-expression in these tumours was associated with tumour differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
100
2
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 38 publications
(66 reference statements)
3
100
2
2
Order By: Relevance
“…There is no sex predilection [19]. However, Lam et al reported that, like other thyroid carcinomas, SCC of the thyroid was more commonly in women in their study [10]. Meanwhile, our SCC cases were all found in men.…”
Section: Discussionmentioning
confidence: 42%
See 4 more Smart Citations
“…There is no sex predilection [19]. However, Lam et al reported that, like other thyroid carcinomas, SCC of the thyroid was more commonly in women in their study [10]. Meanwhile, our SCC cases were all found in men.…”
Section: Discussionmentioning
confidence: 42%
“…The reported incidence ranges from 0.7% to 3.4% [17,18]. This unusual tumor of the thyroid usually occurs in the 5 th to 7 th decades of life [10,15]. The patients we reported were 53, 71 and 66 years old.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations